1970
DOI: 10.1136/pgmj.46.532.71
|View full text |Cite
|
Sign up to set email alerts
|

Kerosene poisoning in children

Abstract: Summary The epidemiological and clinical aspects of 100 cases of kerosene poisoning have been studied. The use of gastric lavage is discussed, and it is considered that this measure is probably valuable in treatment. The importance of preventive measures is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…12 Similar to studies by L. Nouri and K. A1 Rahim, this study also showed a seasonal preponderance in the months of April to June. 13 cough was present in 86 patients (82%) whereas it was found in (83.5%) in Nagi study, (96%) in Mahjoob Al Naddawi study and (67%) in shotal study. [14][15][16] Fever was present in 73 patients (69%) which was (73.8%) in nagi study and (94%) in Mahjoob al-Naddawi study.…”
Section: Discussionmentioning
confidence: 67%
“…12 Similar to studies by L. Nouri and K. A1 Rahim, this study also showed a seasonal preponderance in the months of April to June. 13 cough was present in 86 patients (82%) whereas it was found in (83.5%) in Nagi study, (96%) in Mahjoob Al Naddawi study and (67%) in shotal study. [14][15][16] Fever was present in 73 patients (69%) which was (73.8%) in nagi study and (94%) in Mahjoob al-Naddawi study.…”
Section: Discussionmentioning
confidence: 67%
“…As with other studies improper storage was found to be the main cause of poisong. 4 Fever is frequently seen with kerosene poisoning and may persist for several days.4"0 Seventy-six patients in this study had fever and there was correlation between the extent of lung involvement and the severity and duration of the fever. All patients had a chest X-ray on admission to the hospital, of these 51 were normal and 52 considered abnormal.…”
Section: Seasonmentioning
confidence: 62%
“…A male preponderance is usual with kerosene and other poisonings and accidents. 4 The age distribution of the patients is shown in box 1; the majority were under five years. A seven-day-old baby is included in this series.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we observed that the accidental kerosene ingestion occurred mostly in April corresponds to the early heat wave of summer, which is similar with the experience of L. Nouri and K. Al-Rahim. 11 A very striking feature of this study is the usage of empty bottles of soft drink as the container for kerosene is related to the most of the poisoning. This may be due to the childhood conception of soft drink that misleads those babies to drink kerosene from the same type bottles during thirst.…”
Section: Discussionmentioning
confidence: 99%